The Impact of Energy Consumption and Industrial Value Added on Economic Growth in Central China: Dynamic Panel ARDL Analysis - Liu, Simiao; Chin, Lee; Bala, Umar (International Journal of Energy Economics and Policy, 2025)
Energy consumption and industry value-added are crucial to economic activities and have been a potential priority for China’s domestic economic growth, especially in the resource-rich central region of the Country. The research examines the impact of energy consumption and industry value- added on economic growth in six central Chinese areas from 2000 to 2022. The study employed the PMG estimator during data estimation, along with Quantile and FMOLS regressions for robustness checks. The research utilized disaggregated data on industrial value added, specifically primary, secondary, and tertiary industry value added. The findings indicated that higher energy consumption in primary and tertiary industries significantly stimulates economic growth, while the secondary industry value-added is not significant. Furthermore, capital accumulation and urbanization significantly contributed to economic growth. The labor force indicated a negative effect on growth, possibly due to inefficiencies, low productivity, or structural imbalances in the economy. The research recommended that policymakers ought to consider different patterns of energy consumption in industrial value-added firms for greater economic growth. There is a need for labor market reforms and productivity-boosting policies. Policymakers need to consider the unique economic and energy consumption patterns of Central China when designing and implementing energy policies. A one- size-fits-all approach is ineffective due to regional disparities.